Implementation of Russian Migration Policy in Kuzbass Region in Late XIX - early XX Centuries - V. G. Dorokhov; A. Yu. Karpinets; A. E. Pyanov (Научный диалог)
The article is devoted to the characterization of some problems of the implementation of resettlement-colonization measures in the Kuzbass region (Kuzbass) during the late XIX - early XX centuries. The issues of the dynamics of the resettlement and reserve plots formation in this territory are considered. Attention is paid to the dynamics of the migration flow in the indicated period. Based on the analysis of statistical data, the volumes of the resettlement movement in the cabinet and state-owned villages of the Kuzbass region are presented. The novelty of the study is seen in the fact that for the first time, based on the processing of statistics, the state and dynamics of the resettlement-colonization processes in the Kuzbass region (Kuzbass) during the late XIX - early XX centuries are shown. The differences in the implementation of the resettlement policy in the cabinet and state lands of Kuzbass are demonstrated. The relevance of the study is due to its scientific and social significance. The first one is determined by the fact that this kind of research, based on the analysis of statistical data, is undertaken for the first time. The second point is connected with the need to draw attention to the problems of sustainable socio-economic development of rural territories at present.